Expressions in Fan Culture. Cosplay, Fan Art, Fan Fiction - Ragnhildur Björk Jóhannsdóttir 1993- (2017)
This composition is a BA thesis for Japanese Language and Culture at the University of Iceland. In this essay, I will give the reader a little insight into the world of fan culture and will be focusing on how fans express themselves. Fans get inspired by books, movies and television programmes to create all kinds of fan work; whether it is fan fiction, fan art, doujinshi, cosplay, or any other creations. Furthermore, the thesis will explore fan culture as it presents itself in Japan and compare it to fan culture in Europe and the USA. I will discuss the effect these creations, although mainly fan fiction, has on authors of popular media and on social media and how the Internet has made it easier for fans all over the world to connect, as well as for fans and creators to connect.